The Role of E-Wallet Adoption, Digital Security Perceptions, and Technology Reliability on Digital Payment System Usage Decisions in East Java - Arief Rahman; Ahmad Rizani; Rezty Arizta Putri; Shofiatul Inayah; Deti Kurniati (Westscience Press, 2026)
This study examines the influence of e-wallet implementation, digital security perceptions, and technology reliability on digital payment system usage decisions in East Java. Using a quantitative research approach, data were collected from 150 active digital payment users through a structured questionnaire measured on a five-point Likert scale. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) version 3 to evaluate both the measurement and structural models. The results indicate that e-wallet implementation has a positive and significant effect on digital payment usage decisions, highlighting the importance of usability, system integration, and functional design. Digital security perceptions emerge as the strongest determinant, emphasizing that users’ confidence in data protection and transaction safety plays a critical role in shaping adoption behavior. Technology reliability also shows a significant positive influence, demonstrating that system stability and transaction accuracy are essential for sustaining user trust and continued usage. Overall, the findings suggest that digital payment adoption in East Java is driven by a combination of effective system implementation, strong security perceptions, and reliable technological performance. This study contributes to the digital finance and fintech adoption literature by providing empirical evidence from a regional context and offers practical insights for e-wallet providers and policymakers to strengthen digital payment ecosystems.